2002
DOI: 10.1046/j.1440-1754.2002.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Henoch‐Schönlein purpura and priapism

Abstract: This is the first report of priapism in a child with Henoch-Schönlein purpura. Priapism is a condition rarely seen in childhood. When seen in the paediatric population, it is most often associated with haematological disorders. On a world-wide basis, sickle cell anaemia accounts for the majority of childhood priapism. Failure to treat priapism can lead to serious sequelae, including fibrosis and impotence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…In contrast, Sari et al 13 described a patient with newly diagnosed HSP presenting with priapism secondary to thrombosis of the dorsal vein of the penis, which required a penile prosthesis due to cavernosal necrosis and fibrosis. Lind et al 14 reported a case of a 9-year-old boy with newly diagnosed HSP with priapism treated successfully with caudal anaesthesia and cavernosal aspiration. These two cases are exceptions, as most patients with penile HSP have a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Sari et al 13 described a patient with newly diagnosed HSP presenting with priapism secondary to thrombosis of the dorsal vein of the penis, which required a penile prosthesis due to cavernosal necrosis and fibrosis. Lind et al 14 reported a case of a 9-year-old boy with newly diagnosed HSP with priapism treated successfully with caudal anaesthesia and cavernosal aspiration. These two cases are exceptions, as most patients with penile HSP have a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 Rare cases of thrombosis involving the sagittal sinus, 2,3 tibial/fibular artery, 4 iliac/femoral vein, 5 spermatic vein, 6 and penile venous system (manifesting as priapism) 7 have been reported. 1 Rare cases of thrombosis involving the sagittal sinus, 2,3 tibial/fibular artery, 4 iliac/femoral vein, 5 spermatic vein, 6 and penile venous system (manifesting as priapism) 7 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a review of the published literature and found eight other patients[12345678] with HSP-associated thrombosis [Table 1]. Most patients were treated with anti-inflammatories and anticoagulants.…”
Section: Discussionmentioning
confidence: 99%